The Double Edge of Professional Agency: The Contradictory Roles of Human Resource Professionals in the Implementation of the Parental Leave Policy in South Korea. (October 2020) - Baek, Kyungmin; Choi, Seongsoo
Why do organizations respond differently to social policies? This is an important question because it gives us a clue as to why social progress is often slow even with successful legislation. We argue that HR professionals' conflicting roles within organizations affect modes of organizations' compliance with a law because HR professionals are expected to adjust legal pressure to business interests when translating external requirements into internal policies. How they manage this challenge depends on variation in the development of different dimensions of their professional agency: formalization and substantive empowerment. We demonstrate empirically this argument by taking the case of South Korea's parental leave policy. Using workplace-level data, we find that the presence of formal HR structures predicts that minimal compliance is more likely than is noncompliance, but is less likely than is maximal compliance, and that substantively empowered HR professionals contribute to making both compliance and maximal compliance more probable.